Asesmen Kompetensi Minimum Anak dalam Membangun Fondasi Literasi-Numerasi dan Bagaimana Implikasi pada Pembelajaran Anak Usia Dini: Minimum Competency Assessment of Children in Building the Foundation of Literacy-Numeracy and Its Implications for Early Childhood Learning - Tollo, Vinchensia Theresia; Oka, Gde Putu Arya; Laksana, Dek Ngurah Laba; Dhiu, Konstantinus Dua (Universitas Ngudi Waluyo, 2025)
This study aims to analyze the factors contributing to the low literacy and numeracy skills of fifth-grade students at Piga Elementary School through the AKM test, as well as to formulate strategies to improve these skills starting from Early Childhood Education. The research method used is context analysis with a combination of data triangulation. The results of the study show that students' literacy and numeracy skills are categorized as very low. The low literacy and numeracy skills of students are caused by the lack of adequate stimulation since early childhood education, less varied learning methods, and lack of parental support. Previous studies also support these findings, showing that strong literacy and numeracy skills from an early age are crucial foundations for future learning success. To address this issue, comprehensive efforts are needed, such as improving the quality of learning in Early Childhood Education, actively involving parents, and developing a more relevant curriculum. This study concludes that enhancing literacy and numeracy skills from an early age is a long-term investment in producing intelligent and competitive generations. ABSTRAK Penelitian ini bertujuan untuk menganalisis faktor-faktor yang menyebabkan rendahnya kemampuan literasi dan numerasi siswa di SDK Piga melalui tes AKM, serta merumuskan strategi untuk meningkatkan kemampuan tersebut sejak Pendidikan Anak Usia Dini (PAUD). Metode penelitian yang digunakan adalah analisis konteks dengan kombinasi triangulasi data. Hasil penelitian menunjukkan bahwa kemampuan literasi dna numerasi siswa masuk kategori sangat rendah. Rendahnya kemampuan literasi dan numerasi siswa disebabkan oleh kurangnya stimulasi yang memadai sejak PAUD, metode pembelajaran yang kurang variatif, serta kurangnya dukungan orang tua. Penelitian sebelumnya juga mendukung temuan ini, yang menunjukkan bahwa kemampuan literasi dan numerasi yang kuat sejak dini merupakan fondasi penting untuk keberhasilan belajar di masa depan. Untuk mengatasi masalah ini, perlu dilakukan upaya yang komprehensif, seperti meningkatkan kualitas pembelajaran di PAUD, melibatkan orang tua secara aktif, dan mengembangkan kurikulum yang lebih relevan. Penelitian ini menyimpulkan bahwa peningkatan kemampuan literasi dan numerasi sejak dini merupakan investasi jangka panjang untuk menghasilkan generasi yang cerdas dan kompetitif.